Persepsi Guru Terhadap Implementasi Kurikulum Merdeka - Endang Mitrawati; Sitti Kasmiati; La Ode Nursalam (Jurnal Penelitian Pendidikan Geografi, 2025)
The Merdeka Curriculum was introduced in response to the increasingly dynamic challenges in education, emphasizing flexibility in competency-based learning and the development of students' character. This study aims to understand teachers' perceptions of implementing the Kurikulum Merdeka at Senior High School 1 Batauga. The research employs a qualitative method using a Likert scale. The findings indicate that: 1) teachers' perceptions of the implementation of Kurikulum Merdeka at Senior High School 1 Batauga are generally positive; teachers see it as an opportunity for a more dynamic learning experience. In addition, most teachers have successfully adapted to the approach introduced in the curriculum; 2) regarding the perception of student-centered learning, 52% of teachers responded with Strongly Agree, 40% with Agree, and 8% with Disagree. In terms of student participation, 70% of teachers responded with Strongly Agree and 30% with Agree. Regarding effective learning, 58% of teachers responded with Strongly Agree, while 42% responded with Agree. These results indicate that implementing the Merdeka Curriculum has positively impacted student-centered learning, as evidenced by increased student participation and more effective learning processes.